2021
DOI: 10.1002/cmdc.202100570
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Photothermal Sterilization and Abscess Elimination Research of BSA‐CuS Nanoparticles in vivo

Abstract: The treatment of subcutaneous abscess caused by drug‐resistant bacteria is facing great difficulties and receiving more attention. In this work, we employed BSA‐CuS nanoparticles as a photothermal reagent to apply photothermal therapy (PTT) to combat drug‐resistant bacteria in vitro and subcutaneous abscess in vivo. The BSA‐CuS nanoparticles were found to be stable and biocompatible without cytotoxicity toward NIH3T3 and 4T1 cells. In vitro experiments showed that three species of drug‐resistant pathogens, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Albumin scaffold meanwhile ensures the chemical stability, physiological stability, dispersibility and biocompatibility of the nanoagents [ 12 15 ]. Some studies reported that albumin-biomineralized copper sulfide nanoparticles (BSA@Cu 2−x S NPs) have excellent photothermal transduction effect, good biocompatibility and dispersibility, as well controllable size of the nanomaterials [ 16 23 ]. In 2016, we have shown that BSA@Cu 2−x S NPs have a high photothermal conversion efficiency, good stability and tumor photothermal ablation capacity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Albumin scaffold meanwhile ensures the chemical stability, physiological stability, dispersibility and biocompatibility of the nanoagents [ 12 15 ]. Some studies reported that albumin-biomineralized copper sulfide nanoparticles (BSA@Cu 2−x S NPs) have excellent photothermal transduction effect, good biocompatibility and dispersibility, as well controllable size of the nanomaterials [ 16 23 ]. In 2016, we have shown that BSA@Cu 2−x S NPs have a high photothermal conversion efficiency, good stability and tumor photothermal ablation capacity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%